Often biased but rarely in doubt: How initial reactions to stigmatized applicants affect interviewer confidence. Issue 4 (7th August 2016) - Buijsrogge, Alexander; Derous, Eva; Duyck, Wouter
ABSTRACT: Building on a metacognitive framework of heuristic judgments, we investigate the effect of applicant stigma on interviewers' overconfidence in their (biased) judgments. There were 193 experienced interviewers conducting a face-to-face interview with an applicant who was facially stigmatized or not, and who was visible (traditional interview) or not (partially blind interview), to the interviewer during the rapport-building stage. In traditional interviews, interview judgments of stigmatized applicants were negatively biased, and interviewers reported overconfidence in these judgments. This effect was partially mediated by the interviewer's professional performance during rapport building. Interview procedure moderated both the direct and indirect effect (through professional performance) of applicant stigma on interviewer confidence. Results show that interviewer (over)confidence in biased judgments is driven by the initial effects of, and reactions to, the stigmatized applicant.